Lean Office and digital transformation: a case study in a services company - Besser Freitag, Alberto Eduardo; Santos, Juliana das Chagas; Reis, Augusto da Cunha (Brazilian Journal of Operations & Production Management, 2018)
- Highlights: a high percentage of the Western world workforce works in offices; Value Stream Map, a lean tool, allows waste identification in services companies; Lean Management helps companies to prepare for digital transformation; there is scarce scientific literature ondigital transformation and Lean Office. -Goal: thepurpose of this article is to report the implementation of Lean Office and digital transformation in a services company. - Design / Methodology / Approach: the research method was a qualitative approach, with literature review followed by a case study, and data collected until September 19, 2018. - Results: the comparative results between current and future Value Stream Maps showed consistent improvements in terms of performance indicators. The lead time is expected to fall from 101 hours to 64,65 hours under normal conditions, and from 221 hours to 114,65 hours if there is a need to bypass through process # 6. - Limitations of the investigation: there are limitations in this study.Basically, the time frame until the digitalization of the processes # 1, 2, 3 and 6 have been completed, in order to allow the comparison with the original expectations described in the VSM of the future state. - Practical implications: it was possible to demonstrate how the implementation of Lean principles, techniques, and tools can bring benefits to an IoT solutions provider. - Originality / Value: no records were found on Scopus and Web of Science databases for the search sentence "digital transformation" AND "lean Office", representing a gap to be filled with this study.